Chemoprevention of colorectal cancer in ulcerative colitis: digging deep in current evidence. (3rd April 2017) - Bezzio, Cristina; Festa, Stefano; Saibeni, Simone; Papi, Claudio
ABSTRACT: Introduction: Patients with ulcerative colitis (UC) have an increased risk of developing colorectal cancer (CRC). Surveillance colonoscopy is currently recommended for patients with long-standing extensive colitis for reducing CRC risk. Chemoprevention is an attractive complementary strategy. Areas covered: Inflammation is a major determinant of CRC risk and is potentially modifiable. Reducing inflammation is supposed to reduce CRC risk. Several medications have been evaluated in this setting: 5-ASA, thiopurines, anti-TNFα agents and ursodeoxycholic acid (UCDA) in patients with associated primary sclerosing cholangitis (PSC). This review offers a critical evaluation of current evidence of the potential chemopreventive effect of such medications. Expert commentary: No randomized controlled trials have been performed and the available evidence come from observational studies. Although biological plausibility supports a chemopreventive role of the aforementioned agents, the overall evidence of efficacy is weak because of several methodological limitations of the studies. Indirect epidemiological evidence, biologic plausibility and results of meta-analyses reasonably support a potential chemopreventive effect of 5-ASA. Available evidence does not support a specific chemopreventive effect of purine analogues and anti-TNFα medications, despite their efficacy in the management of inflammatory bowel disease. Data addressing UDCA and folate supplementation are inconclusive. Limited data are available for statins.